Homoptera Coccoidea new for Italy (Bollettino di zoologia agraria e bachicoltura, 2024)
The presence in Italy of the following species of scale-insects is recorded: Chnaurococcus parvus (Borchsenius), Rhizoecus caesii Schmutterer, Spinococcus calluneti (Lindinger), Trionymus dactylis Green (Fam. Pseudococcidae), Rhizaspidiotus balachowskyi Kozar & Matile Ferrero (Fam. Diaspididae).
Keywords: Scale insects; new records; Italy